Factors influencing perceived importance of haemodialysis adherence among end stage kidney failure patients in tertiary care centres in Nepal - Pramita Shrestha; Anisha Koirala; Prajwal Satyal; Ashish Mani Bhurtel; Biraj Man Karmacharya (PLoS ONE, 2026)
Background Chronic Kidney Failure is a significant global public health concern requiring kidney replacement therapy such as dialysis. Perception of the importance of adhering to dialysis helps to determine how patients interpret and interact with the influencing attitude, thoughts and behaviours towards adhering to dialysis. This study aimed to assess the perception of the importance of adherence to haemodialysis and its associated factors among end-stage Kidney failure patients in tertiary care centres in Nepal. Methods This was a cross-sectional study conducted from May to August 2025 in two tertiary care centres in Nepal that included patients undergoing hemodialysis aged 18 years and above. The outcome variable was perception of the importance of adherence to dialysis and was measured using The End Stage Renal Disease Adherence Questionnaire (ESRD-AQ). The independent variables were socio-demographics, dialysis-related characteristics and accessibility factors. Results Among 283 hemodialysis patients in the study, their mean age was 50.6 years with higher prevalence of good perception (91%) among single [APR (adjusted prevalence ratio):1.12; 95% CI (confidence interval): 1.03–1.21)] and parents accompanying patients (APR:1.14; 95% CI:1.01–1.28) compared to married, and non-parent accompanying patients respectively. Conclusion The study showed good perception of hemodialysis adherence, especially among singles and those accompanied by their parents.